Analisis Peran Manajemen Keuangan Dan Implementasi Pada Kelompok Usaha Mikro Kecil Dan Menengah (UMKM) Terpadu Salimbai Kecamatan Taman Rajo Kabupaten Muaro Jambi - Rezki Febriani; Sissah Sissah; Ogi Saputra (Jurnal of Management and Social Sciences, 2023)
Micro, small and medium enterprises (MSMEs) currently have a very important role as a locomotive driving the economy and eradicating poverty. In addition, MSMEs are one of the most efficient economic sectors for entrepreneurship development which provide solutions to problems of poverty, insecurity, unemployment and can provide solutions for population explosion in a more modern direction in the current era of globalization. Based on data obtained from the Ministry of Cooperatives and Micro, Small and Medium Enterprises (MSMEs) it shows that the number of MSMEs in Indonesia in 2013 was around 57 million units. In the 2012-2013 period, there was an increase in the number of business units by 2.41%. The data shows that MSME is one of the supporting sectors of the economy in Indonesia.